Model of Strengthening Human Resources Through the Fisheries Resource Utilization Makassar - Hj. Dahliah (Journal of Education and Vocational Research, 2016)
This study aims first to analyze the strengthening of human resource models with variable quality fishing gear insyani resources, involvement in economic activities and the local culture through economic capacity in the utilization of natural resources and the second to analyze fisheries MP3EI program didaaerah Sulawesi economic corridor that has not been synchronized. Implementation of these variables in strengthening human resources in coastal communities. This research was conducted in the coastal area of Makassar, precisely the small island-island Makassar in (two) years. The study population was all fishermen are categorized as poor. Slovin sample was determined with the theory that those who have a poor criterion of 99 respondents.The urgency of research, human resources strength problems, need to be identified at the planning MP3EI program ekonomi.agar growth can go hand in hand between the economic corridor and central Sulawesi. Outcomes research result in models of reinforcement of human resources, strengthening human resources design gran sesuiaThe urgency of research, human resources strength problems, need to be identified at the program ekonomi.agar growth can go hand in hand between the economic corridor and central Sulawesi. Outcomes research result in models of reinforcement of human resources, strengthening human resources design gran sesuia purpose MP3EIresearch initerinspirasi of theory Nurkses (1953), which states that the causes of poverty or weakening of human resources led to the theory of the vicious circle of poverty (Vicions Circle of poverty) put forward by the six elements, namely keterbelakanganataumelemahnya human resources, low investment, omission lack of capital, low savings and low productivity, method used is quantitative method. Model Strengthening human resources with quantitative methods with associated variables later via Path analysis.